Assassination of the French deputies at Ratstadt, April 1799 (engraving) - Auteur inconnu (Wikimedia Commons, 1860)
Notice iconographique issue de Wikimedia Commons. Titre: Assassination of the French deputies at Ratstadt, April 1799 (engraving). Assassination of the French deputies at Ratstadt, April 1799 (engraving)
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons